Drysdalin, an antagonist of nicotinic acetylcholine receptors highlights the importance of functional rather than structural conservation of amino acid residues - Chandna, Ritu (FASEB Bioadv, 2019)
Snake venom neurotoxins are potent antagonists of nicotinic acetylcholine receptors (nAChRs). Here, we describe a novel member of class 3c long‐chain neurotoxin drysdalin from the venom of Drysdalia coronoides. Drysdalin lacks three of the eight conserved classical functional residues critical for nAChRs interaction. Despite such a drastic alteration of the functional site, recombinant drysdalin showed irreversible postsynaptic neurotoxicity with nanomolar potency and selectively antagonizes the rodent muscle (α1)(2)β1δε, and human α7 and α9α10 nAChRs, but had no significant activity at the human α3β2, α3β4, α4β2, and α4β4 nAChRs. Substitution of Leu34 and Ala37 residues with the conserved Arg had minimal impact on the potency whereas conserved Phe replacement of residue Arg30 substantially reduced or abolished inhibitory activity. In contrast, truncation of the 24‐residue long C‐terminal tail leads to complete loss in (a) activity at α9α10 nAChR; and (b) irreversibility with reduced potency at the muscle and α7 nAChRs. Overall, the non‐conserved Arg30 residue together with the uniquely long C‐terminal tail contribute to the inhibitory activity of drysdalin at the nAChRs suggesting, at least for drysdalin, functional rather than sequence conservation plays a critical role in determining the activity of the toxin.